COMPARATIVE TESTS OF FIVE ORGANOPHOSPHOROUS INSECTICIDES AGAINST LAB-BRED AND WILD CAUGHT LARVE OF ANOPHELES STEPHENSI MYSORENS1S IN SOUTHERN IRAN - A. V. Manouchehri; M. Khademi; N. Eshirhi (Tehran University of Medical Sciences, 1974)
Five organo-phosphorous compounds were tested against lab-bred and wild caught larvae of Ano pliclcs stcphclIsi nrysorcnsis at the Kazeroun Medical Research Station, southern Iran, during May-june, 1974. This study showed that as the larvae grew their tolerance to the insecticides tested increased up to 5 times more than that of day-old larvae. When Iate 3rd and early 4th instal' larvae of wild caught .•111. stcnhcnsi mysorcnsis were tested against organo-phosphorous compounds, the LC50's increased up to 2 times more than those of the same instal' larvae of lab-bred mosquitoes of this species.